The Chinese-Indonesian Community, Constitutional Debates, and Citizenship: Navigating Identity and Rights - Avicena, Sarah; Judith, Alex Prima; Kusumaningsih, Srivan (Indonesia Discourse, 2024)
This study explores the complex interplay between ethnicity, citizenship, and national identity in Indonesia, particularly focusing on the Chinese-Indonesian community. This research critically examines the historical and ongoing struggles for recognition and rights of the Chinese-Indonesian minority, particularly in relation to constitutional debates surrounding citizenship and identity. The study investigates the ways in which the Chinese-Indonesian community, often marginalized and subjected to discriminatory policies, has navigated the evolving definitions of national belonging in Indonesia's post-independence period. Drawing on primary sources such as constitutional documents, legislative debates, and testimonies from Chinese-Indonesian individuals, the research highlights the fluctuating status of this community from Indonesia’s early years as a republic to its modern-day democracy. The study emphasizes the centrality of constitutional reform in shaping the community's legal rights, particularly the struggle for equality and protection from discrimination in the face of political shifts and societal prejudice. This research makes a vital contribution to understanding the tensions between ethnicity, citizenship, and national identity in a multiethnic society like Indonesia. It provides insights into how legal frameworks and political debates have influenced the integration of ethnic minorities, particularly the Chinese-Indonesian group, into the broader national narrative. Additionally, it underscores the urgency of addressing historical injustices and promoting inclusive citizenship, particularly through ongoing debates on equality, recognition, and human rights in contemporary Indonesia. This work is crucial for informing future discussions on multiculturalism, citizenship, and identity in Indonesia and beyond.